Solid Waste Management Practice in Burdwan Municipality, West Bengal: An Overview - Sheikh, Surat (Journal of Innovation in Academia, 2023)
This study provides an overview of solid waste management practices in Burdwan Municipality and identifies sources of waste generation. The study primarily relies on both primary and secondary data collected from Burdwan Municipality. A prepared questionnaire was utilized during field studies conducted in the wards of Burdwan Municipality. Secondary data, available in the form of reports and documents from the year 2019, were also employed. Tabular presentations, flowcharts, pie charts, statistical tools, and techniques were used for the study. A flowchart model is employed to describe the current practices of solid waste management in Burdwan. Municipal solid waste is classified and identified based on waste characteristics. Biodegradable waste is the primary source of municipal solid waste (MSW) generation in Burdwan town. Commercial places generate more MSW than institutions, while the top contributors from residential premises are low-income group (LIG) households. This study observes a mismatch between MSW generation and available infrastructure, as well as poor management practices. MSW accumulates day by day, leading to environmental pollution. However, this issue could be resolved by adopting a reuse and recycle mechanism to convert waste into useful products.